The emergence of government information services in British Malaya: Exploring the antecedent growth of public relations in Malaysia - Idid, Syed Arabi; Souket, Rizwanah (2017)
This article covers the emergence of the first form of Governmental information services in Malaysia. The article gives an account of the importance of the information services in the historical development of the Malaysian Public Relations. The objective of this paper is to look into the origin of the first formal Information Agency in British Malaya and to evaluate how the early information services aided the British economic consolidation during the economic boom and the economic depression years in British Malaya (1910 -1934). The early colonial information services has always been linked to the prolific use of propaganda especially during World War 1 and World War 2 (Idid, 1995). Most often these services were in the form of propaganda agencies under the controlling governments and were often labelled as ‘information’ offices or committees. Some of the common examples include- the office of war information (OWI: 1942-1945), the committee on public information (1917-1919) and the Ministry of Information formed in 1939 that was the central government department responsible for publicity and propaganda in the Second World War. According to Anderson (1989) many of the early information offices that were run by the local governments have been the forerunners of the PR sector in the UK. The current paper attempts to trace the history of the information offices in Malaysia and explores its evolution as a precursor to the PR sector in Malaysia.